Seroprevalence and risk factors for C. burentii infection in camels in Egypt. (February 2020) - Selim, Abdelfattah; Ali, Abdel-Fattah
Highlights: The seroprevalence of C. burnetii in camels was 22 % in Egypt. The infection is more prevalent in arid condition areas. The prevalence rate of C. burnetii increased in aged female especially with history of abortion. The season, presence of tick and contact with small ruminants had potential risk on prevalence of C. burnetii infections in camels. Potential risk of infection for humans and animals. Abstract: Q fever caused by Coxiella burentii, gram negative obligate intracellular bacterium. The disease has been reported in wide range of animals especially ruminants. The available data about the prevalence of Q fever in camels in Egypt are limited. Therefore, the present study aimed to investigate the seroprevalence of C . burnetii among camels and identify the risk factors associated with infection. A total 315 serum samples were collected from three governorates in Egypt during 2018 and examined by an indirect Enzyme linked Immunosorbent Assay (ELISA). The obtained results were subsequent analyzed by chi-square and logistic regression. Generally, the seroprevalence of C. burnetii among camels was 22 %. The results revealed that the seroprevalence of C. burnetii increased in aged female camels in comparison with young one and was higher also in female with history of abortion (OR = 4.6, 95%CI: 2.46–8.76). The infection was significantly increased during autumn season (OR = 9.3, 95%CI: 4.23–20.5). Besides, camels in contact with small ruminants showed high level of infection (OR = 1.12, 95%CI: 0.65–1.93) or camel with heavy tick infestation (OR = 1.08, 95%CI: 0.60–1.92). Our report confirms that the seroprevalence of C. burnetii among camels in Egypt and appropriate control measures should be taken to reduce the transmission of infection to other animal species or human.